2015
DOI: 10.1016/j.agsy.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and economic impacts of agri-environmental schemes designed in French West Indies to enhance soil C sequestration and reduce pollution risks. A modelling approach

Abstract: Agri-environmental schemes (AESs) are the main public policy instrument used in Europe to encourage farmers to adopt environmentally-friendly farming practises. Some AESs designed in French West Indies to replace N fertilizers with composts to reduce nitrate pollution and enhance C sequestration have been unsuccessful because few farmers adopted them despite the subsidies offered for the provision of environmental benefits. To explain this low adoption rate, we assessed the agri-environmental and economic impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The cropping system characteristics required to improve the contribution of agriculture to sustainable development may help to identify relevant economic incentives, such as agrienvironmental schemes that would encourage farmers to adopt environmentally-friendly farming practices such as reducing the impact of pesticides on water bodies. Examples of such incentives already exist in the French West Indies, such as that which has been prototyped to favour the adoption of composts to enhance carbon sequestration in yam-based cropping systems (Blazy et al, 2015). Direct or indirect subsidies are important drivers of changes to practices because fixed and transaction costs are key drivers for the adoption of new cropping systems (Barreiro-Hurlé et al, 2010).…”
Section: Usefulness Of the Methods To Decision-makersmentioning
confidence: 99%
“…The cropping system characteristics required to improve the contribution of agriculture to sustainable development may help to identify relevant economic incentives, such as agrienvironmental schemes that would encourage farmers to adopt environmentally-friendly farming practices such as reducing the impact of pesticides on water bodies. Examples of such incentives already exist in the French West Indies, such as that which has been prototyped to favour the adoption of composts to enhance carbon sequestration in yam-based cropping systems (Blazy et al, 2015). Direct or indirect subsidies are important drivers of changes to practices because fixed and transaction costs are key drivers for the adoption of new cropping systems (Barreiro-Hurlé et al, 2010).…”
Section: Usefulness Of the Methods To Decision-makersmentioning
confidence: 99%
“…A recently conducted GHG inventory analysis indicated that N fertilizers and lime spreading were key causes of GHG emissions (Colomb et al, 2014). Replacement of inorganic fertilizers with organic amendments in agriculture has been explored as a means of managing soil fertility in a more sustainable manner (Blazy et al, 2015;Sierra et al, 2016). This situation is particularly critical, as the combination of climate change and intensive agricultural practices may lead to a decrease in soil organic matter content and thus an increase in CO2 emissions (Sierra et al, 2015).…”
Section: Study Area and Farming Systems Contextmentioning
confidence: 99%
“…In some studies conducted in developed and developing countries, the results revealed that traditional supply-based policies alone may unlikely guarantee an appropriate technological innovation level by farmers [15]. For instance, in most tropical countries, failures recorded in compositing aroused from the dearth of attention paid in the planning stage to understand the demand, economic and technical aspects involved in organic farming methods [16,17].…”
Section: Introductionmentioning
confidence: 99%